Les anciens et la Nation : quelques réflexions sur les utilisations de l’Antiquité classique à l’Instituto Histórico e Geográfico Brasileiro (1840-1860) - Rodrigo Turin (L'Atelier du CRH)
The aim of the present article is to discuss some limitations and problems raised when applying the Koselleck’s model of modern concept of History into linguistic spaces other than that studied by this German historian. The reconstruction of the ways in which the ancients are used by the Instituto Histórico e Geográfico Brasileiro, considered together with the intellectual contexts as well as the writing genres enrolled in each text, enable the comprehension of different means to represent the past, emphasizing its specificities and contingencies.